2016
DOI: 10.3233/rnn-150600
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke gaseous hypothermia increases vascular density but not neurogenesis in the ischemic penumbra of aged rats

Abstract: Long-term hypothermia may be a viable clinical approach by simultaneously targeting multiple processes including better tissue preservation, enhanced vascular density and improved behavioral performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Epidemiological studies have found that morbidity of human stroke positive correlate to age, and aged brain does not respond exactly to ischemia compared to the young brain ( Popa-Wagner et al, 2006 ; Buga et al, 2014 ; Sandu et al, 2016 ). Based on this we will establish MCAO model in aged rats to observe TFC neuroprotective effects and its mechanism in future study, which are closer to the clinic and more persuasive.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have found that morbidity of human stroke positive correlate to age, and aged brain does not respond exactly to ischemia compared to the young brain ( Popa-Wagner et al, 2006 ; Buga et al, 2014 ; Sandu et al, 2016 ). Based on this we will establish MCAO model in aged rats to observe TFC neuroprotective effects and its mechanism in future study, which are closer to the clinic and more persuasive.…”
Section: Discussionmentioning
confidence: 99%
“…Age is a principal risk factor for stroke. Previous studies showed that aged brain is capable of mounting a vigorous angiogenic response after stroke; however, the vast majority of angiogenic response genes showed delayed upregulation in the aged rats [ 37 , 38 ]. The Notch pathway is an ancient intercellular signaling mechanism, which is fundamental for the development of human tissues, organs, and systems.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical application and feasibility in stroke patients, however, have been hampered by the logistic challenges of long duration cooling in humans (24–48 h) and concerns about rebound ICP complications during rewarming (Schwab et al, 1998 , 2001 ). Few studies have investigated hypothermia after experimental stroke in aged animals, and those that have (long duration gaseous hypothermia, 24–48 h) demonstrated temporary neuroprotection (Florian et al, 2008 ; Joseph et al, 2012 ; Sandu et al, 2016 ; Vintilescu et al, 2016 ). ICP, and thus rebound elevations during rewarming, however, were not measured in these studies.…”
Section: Discussionmentioning
confidence: 99%